Financial Free Zones and Legal Autonomy: A Study of ADGMC and DIFCC - Heikal, Sherif (Advances in Social Sciences Research Journal, 2025)
The research investigates the institutional autonomy and legal functionality of the Dubai International Financial Centre Courts (DIFCC) and the Abu Dhabi Global Market Courts (ADGMC) as hybrid judicial systems operating within the United Arab Emirates (UAE). The courts achieve their unique legal transplantation and selective modernization status through their adoption of English common law and their appointment of foreign judges and procedural independence from the UAE’s federal and Sharia-based judiciary. This research evaluates the rule-of-law performance and enforcement challenges and investor perceptions of these institutions through an analysis of statutory frameworks and landmark case law and comparative studies with global financial jurisdictions including the Singapore International Commercial Court and the Qatar Financial Centre Courts. The article demonstrates that DIFCC and ADGMC achieve legal certainty for international investors through their structural separation from the federal judiciary yet this creates ongoing legal fragmentation and jurisdictional asymmetry. The research demonstrates that financial free zone courts in the UAE function as a strategic market-driven legal autonomy model which works well for commercial governance but remains limited in national integration. The research presents policy recommendations about sustaining hybrid legal systems while maintaining systemic coherence.